Predator community and prey dynamics : a case study of roe deer and re-colonizing fox, lynx and wolf - Arbieu, Ugo (SLU/Dept. of Ecology, 2012)
The role of predation is a central question in ecology and population dynamics. In South-central Sweden, the predator community has gone through drastic changes over the last fifty years with the progressive recovery of three large predators: the fox (Vulpes vulpes), recovering after a sarcoptic mange (Sarcoptes scabiei) outbreak, the lynx (Lynx lynx) and the wolf (Canis lupus), the two latter re-colonizing the region after a massive population persecution at the beginning of the 20th century. These three species potentially prey upon roe deer (Capreolus capreolus). Although it is one of the most common ungulate species in Europe, the combined effect of several predators on its survival is poorly documented. The objective of this study was therefore to infer how roe deer responds to the changes in a gradually increasing multipredator system, and to estimate the consequences for population growth rate.